2010
DOI: 10.1007/s10750-010-0498-y
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrate community dynamics in a temperate European Atlantic river. Do they conform to general ecological theory?

Abstract: Spatial and temporal dynamics of macroinvertebrate communities have usually been linked to several environmental and anthropic factors. The aim of this study is to elucidate how important are these factors in structuring macroinvertebrate communities from temperate regions. Regarding the macroinvertebrate number of taxa, the Habitat Template Model, the Dynamic Equilibrium Hypothesis and the Intermediate Disturbance Hypothesis will be tested in order to know how important the diversity of instream elements and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Phenological patterns and their influence on community metrics were important to our findings. Others observing seasonal taxonomic shifts have attributed them to various causal factors, including life cycle phenologies (Butler 1984, Johnson et al 2012, seasonal changes in food resources (Vannote 1980, Hawkins and Sedell 1981, Álvarez-Cabria 2011, and seasonal patterns of physicochemical variables such as stream temperature (Vannote and Sweeney 1980). Others have observed these factors are related given that taxa emergence patterns may be synchronized with environmental conditions that vary with seasonal influence (Vannote et al 1980).…”
Section: Summary Context and Significancementioning
confidence: 99%
“…Phenological patterns and their influence on community metrics were important to our findings. Others observing seasonal taxonomic shifts have attributed them to various causal factors, including life cycle phenologies (Butler 1984, Johnson et al 2012, seasonal changes in food resources (Vannote 1980, Hawkins and Sedell 1981, Álvarez-Cabria 2011, and seasonal patterns of physicochemical variables such as stream temperature (Vannote and Sweeney 1980). Others have observed these factors are related given that taxa emergence patterns may be synchronized with environmental conditions that vary with seasonal influence (Vannote et al 1980).…”
Section: Summary Context and Significancementioning
confidence: 99%
“…For instance, Stenger-Kovács, Lengyel, Crossetti, Üveges, and Padisák (2013) demonstrated that high-and low-profile (i.e., tall and short stature, respectively; Passy, 2007) diatom species increased with increased solar irradiance, because higher irradiance levels can penetrate the algal matrix and can reach the deeper layers of the epilithon (Dodds, 1992). In addition, macroinvertebrate scrapers and predators reached their highest abundance during summer due to maximal resource levels (Álvarez-Cabria, Barquín, & Juanes, 2010). Moreover, biotic interactions, such as grazing and predation, are also important in the context of community assembly (Abe, Uchida, Nagumo, & Tanaka, 2006;Bolam, Rollwagen-Bollens, & Bollens, 2019;Vilmi, Tolonen, Karjalainen, & Heino, 2017), which can lead to temporal variation in lotic community structures (Fitzgerald et al, 2017;Rosemond et al, 2000;Tonkin et al, 2018;Yang, Tang, & Dudgeon, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This is a multivariate permutation procedure widely used with macroinvertebrate assemblages (e.g., Álvarez-Cabria et al, 2011;Almeida et al, 2013) to verify similarity in their composition between sampling sites. This test returns an R value estimating the strength of sampling sites separation varying from 1 (higher similarity) to 0 (no similarity) (Clarke, 1993).…”
Section: > Biological Comparison Of Sitesmentioning
confidence: 99%